Bioreactor systems for micropropagation of plants: present scenario and future prospects - Murthy, Hosakatte Niranjana; Joseph, Kadanthottu Sebastian; Paek, Kee Yoeup; Park, So Young (Frontiers in Plant Science, 2023)
Plant micropropagation has been adapted in the fields of agriculture, horticulture, forestry, and other related fields for large-scale production of elite plants. The use of liquid media and adoption of bioreactors have escalated the production of healthy plants. Several liquid-phase, gas-phase, temporary immersion, and other modified bioreactors have been used for plant propagation. The design, principle, operational mode, merits, and demerits of various bioreactors used for the regeneration of propagules, such as bulblets, cormlets, rhizomes, microtubers, shoots (subsequent rooting), and somatic embryos, are discussed here. In addition, various parameters that affect plant regeneration are discussed with suitable examples.